The relationship of depression levels and arterial stiffness in hemodialysis patients (Annals of Medical Research, 2021)
Aim: The most common psychiatric disorder in hemodialysis (HD) patients is depression and is associated with morbidity and mortality. The relationship between depression and arterial stiffness in this patient group is a new field of study and data are limited. The aim of this study is to examine depression, arterial stiffness and other potentially relevant laboratory parameters in HD patients.Materials and Methods: The study included 58 chronic renal failure patients who underwent hemodialysis for at least 3 months, and the Beck Depression Inventory (BDI) was applied to the participants by the researcher. Pulse Wave Velocity (PWV) figures of the patients were measured on the day the inventory was applied, and laboratory results were obtained within the same month.Results: Depressive symptoms were determined in 27.6% of the patients, and the severity of depression was 25.9% moderate, 5.2% severe. When patients with and without depressive symptoms were compared, PWV (9.3 ± 1.9 vs. 7.8 ± 2.5, P = 0.04) and phosphorus (5.4 ± 1.5 vs. 4.4 ± 1.1 p = 0.008) levels were significantly higher in the depressive group, while calcium (8.3 ± 0.9mg / dL vs.8.8 ± 0.5mg / dL p = 0.018) levels were significantly lower. Phosphorus level (odds ratio [OR] 2.163; 95% CI 1.174--3.982; p = 0.013) and PWV (OR 1.403; 95% CI 1.018--1.932; p = 0.038) were found as independent predictors for depression in multivariate analysis. Conclusion: One of the serious problems affecting the quality of life in HD patients is depression. In our study, it has been shown that there is an irrelevant relationship between depression and arterial stiffness and phosphorus levels in HD patients.
Keywords: Arterial stiffness; calcium; depression; hemodialysis; phosphorus